Concepts and Development of Islamic Science in the History of Science - Arditya Prayogi; Riki Nasrullah (Yayasan Adra Karima Hubbi, 2024)
Islam is not only understood as a religion. He can also be understood as forming human civilization by developing a scientific tradition based on divine guidance. This article aims to provide an overview of how the conception of Islamic science is seen from the historical development of science itself. This article was written using a qualitative approach using the form of library research. From the results of the study, it is clear that in Islam, the tradition of developing knowledge is not something foreign. Islam makes reason, as well as revelation, a way to gain knowledge. Furthermore, scientific discourse from the time of the Prophet to the Umayyad dynasty continued to develop in various phases and could be said to peak during the Abbasid period and increasingly offered various new discourse dynamics.